2016
DOI: 10.1016/j.apjtm.2015.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of intestinal parasite infections among patients in local public hospitals of Hail, Northwestern Saudi Arabia

Abstract: This is the first study highlighting that intestinal parasites are still an important public health problem in Northwestern Saudi Arabia. Therefore, health education would be the best way to prevent from intestinal parasite infections which are mainly food borne diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
16
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 17 publications
4
16
1
1
Order By: Relevance
“…These factors give the optimum conditions for the growth and transmission and increase the probability of exposure to intestinal parasites [ 5 – 7 ]. Also, it has been affected by the used diagnostic methods and the number of the investigated stool samples [ 8 ]. The major tracks for transmission of intestinal parasites are the contamination of food or drinking water or personal contact via fecal-oral route [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These factors give the optimum conditions for the growth and transmission and increase the probability of exposure to intestinal parasites [ 5 – 7 ]. Also, it has been affected by the used diagnostic methods and the number of the investigated stool samples [ 8 ]. The major tracks for transmission of intestinal parasites are the contamination of food or drinking water or personal contact via fecal-oral route [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…As well known, Saudi Arabia is considered one of the largest destinations of expatriate workers, particularly the food handlers and catering staff, from different countries such as Bangladesh, Philippine, India, Indonesia, Pakistan, Sri Lanka, and Egypt. All of these countries are known to be endemic with many diseases including those caused by intestinal parasites [ 8 ]. Many studies in different regions of Saudi Arabia monitored a high prevalence of infection with intestinal parasites among specific populations such as food handlers (23%), school children (33.8%), expatriates (14.9% to 55%), and Saudi and Non-Saudi patients attending hospitals (39.7% to 77.1%) [ 8 , 10 – 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first epidemiological study on IPIs conducted in this large urban center. Current public policies and international guidelines related to IPIs focus almost exclusively on soil transmitted helminths (STH) 10 - 12 , however, many recent studies have found a shift in community profiles of IPIs from a predominance of STH to protozoans 13 - 16 . Therefore, this cross-sectional study, following the Strengthening the Reporting of Observational Studies in Epidemiology Guidelines (STROBE), assessed the socioenvironmental conditions and prevalence of IPIs in slums of Rio de Janeiro, RJ State, Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Las infecciones por coccidios intestinales se encuentran ampliamente distribuidas en el mundo, detectándose tasas de prevalencias muy variadas: China (12%) 8 , Nepal (5,6%-14,1%) 9 , Polonia (5,4%) 10 , India (1,13-31,29%) 11,12 , Arabia Saudita (19,23%) 13 , Nigeria (2,2-32,2) 14 , Costa de Marfil (3,9-7,7%) 15 , Etiopía (7,9-20,8%) 16 , Libia (0.9-13%) 17 . Para países de Latinoamérica, se han encontrado cifras de prevalencia variables similares, incluyendo Guatemala (7,14-13,7%) 18 , México (9,,4%) 19,20 , Argentina (1,3%) 21 , Perú (4->40%) 22 .…”
Section: Introductionunclassified